A Visualisasi Social Media Analytics Pada Akun Media Sosial Pemerintah Kota Kediri - Ellya Nurfarida; Benni Agung Nugroho; Fery Sofian Efendi (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
One of the factors that influence the government’s performance is the well-socialized work program. The socialization of the local government of Kediri was carried out either through television advertisements, newspapers, billboards, and social media. The process of measuring the performance of the socialization of work program can be done if there is data in form of statistical descriptive that can be presented. Of the various media used to convey work program information, only social media can present data in the form of statistical descriptive because social media contain data insight such as number of followers, number of posts, number of likes, number of shares, and number of comments. The data is unstructured which can be a representation of the performance of each service in Kediri Local government called brand reputation. indirect data retrieval process can be done, must go through web scraping which can retrieve unstructured data on the web to be processed in our database. the stages of web scraping are data capture, data extraction, and data visualization. The results of data visualization will be presented in graphical form using google data studio so that it is easier to analyze and represent to the head of Kediri Local Government. Web scraping is done using the python programming language and data extraction using Microsoft excel. the desired result of the study is the ranking of the performance of each Kediri City Local Government service in socializing work programs through social media which can be measured based on data insight.